Lesão por pressão em adultos internados por COVID-19: estudo caso-controle - Oliveira, Isabella Gerin de (Universidade Federal de São Carlos, 2024)
Incidents related to healthcare constitute a public health problem. One of the most frequently reported adverse events is pressure injury (PI). The COVID-19 pandemic has worsened this scenario, leading to an increase in the number of prolonged hospital admissions requiring intensive care and invasive respiratory support. Institutions needed to prepare to offer health care with safety and quality. Understanding the characteristics of patients hospitalized with COVID-19 associated with the development of PI and lethality can help define care and resource allocation strategies to prevent adverse events. Objectives: The present study aimed to identify risk factors associated with the development of PI and lethal outcome in adult individuals hospitalized with SARS due to COVID-19 in a public university hospital. Methods: Nested case-control study of the development of PI in adult patients hospitalized with COVID-19 at HU-UFSCar. The cases and controls were selected from a sample used for the Cohort Study of lethality of adult individuals hospitalized for COVID-19 between March 2020 and February 2021 (Study 1). Only in the Cohort Study, the patients transferred from service, without information on discharge/death, were excluded. For the selection of the Case-control Study (Study 2), participants were matched by sex, age and date of hospitalization. The independent variables (exposure) evaluated were sociodemographic, clinical and health care-related characteristics. Data collection was carried out from medical records using an electronic form (RedCap). The database was exported to a Microsoft Excel® spreadsheet and evaluated using Epi Info 7 software and IBM SPSS software, version 25, where uni and multivariate logistic regression analysis (Backward) was performed. Results: The study enrolled 373 individuals, with mean age of 61.2 years, 56.3% male, with a PI incidence rate of 17.2%. In the cohort study (Study 1), after excluding individuals transferred from an institution, without information on the outcome, the sample consisted of 349 individuals, with a mortality rate from COVID-19 of 15.3%. The characteristics associated with higher mortality were being from another municipality (OR 4.15), having kidney disease (OR 4.20), hydroeletrolitic disorders (OR 3.43), having needed sedatives/anesthetics (OR 11.71) or invasive mechanical ventilation (OR 3.93). In the case-control study of the development of PI (Study 2), a sample of 202 participants was selected (52 cases and 150 controls), regardless of whether the outcome was discharge, death or transfer. The characteristics associated with the development of PI were previous diagnosis of neurological disease (OR 3.74), diabetes (OR 4.51), gastrointestinal tract disease (OR 5.42), use of sedative/anesthetic drugs (OR 18.06), the development of edema (OR 2.84) and length of stay (OR 1.07). Conclusion: In adults hospitalized with COVID-19, lethality appears to have been influenced by the greater severity, but also by the lack of resources with waiting time for transfer between municipalities, and by the difficulty in maintaining the fluid and electrolyte balance. Individuals who developed PI made more use of sedative or anesthetic drugs, had more gastrointestinal tract disease, diabetes or neurological disease and had a longer hospital stay, and had also more frequently developed edema during hospitalization.
Pressure Injuries in adults hospitalized for COVID-19: case-control study
Keywords: Lesão por pressão; Fatores de risco; COVID-19; Segurança do paciente; Letalidade; Pressure injury; Risk factors; COVID-19; Patient safety; Lethality; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE DOENCAS CONTAGIOSAS